Modelo Alternativo De Funcionamiento Del Sistema Turístico: Teoría De Enjambres Del Turismo Mundial - Zaquinaula, Manuel Antonio Abarca (European Scientific Journal, ESJ, 2017)
The present theory was developed based on the alternative model of operation of the tourist system proposed by the author (based on the models of Roberto Boullón, Neil Leiper, and OMT). It has to do,with a systemic-mechanical approach with harmonious, coordinated, and routine functioning among its four parts (governing body of the tourist system, real-potential demand, geographic space, and tourist offer). Also, it obtains greater efficiency and profitability during the course of its operation. This theory explains that the tourist development of the planet must be based on the correct functioning of the tourist systems of the world. To improve the effectiveness of the management of the global tourism, it must be structured as follows; World tourism = interconnection of tourist swarms, tourist swarms = entanglement of two or more supra tourist systems, supra tourist systems = link between two or more tourist molecules, tourist molecules = union of two compatible tourist systems. A tourist system, therefore, can be formed in any of these destination: a canton, province, region, country, and any other destinations that do not necessarily have political limits. This study explains how tourist molecules, supra tourist systems, and tourist swarms are formed. It highlights the importance of understanding, at the first instance, the alternative model of operation of the tourist system. This is because in its compression lies the basis of the effectiveness and development of global tourism.